KEMAMPUAN PENGIKUT MEMBERI PENGARUH TERHADAP PEMIMPIN - Christine Winstinindah Sandroto (Center for Economic Studies Universitas Katolik Parahyangan, 2009)
The aim of this article is to find whether it is possible for follower to influenced the leader. Here we have five followership style: alienated, passive, conformist, effective, and pragmatic survivor according to two dimensions. The first dimension is the quality of independent, critical thinking versus dependent, uncritical thinking. The second dimension is active versus passive behavior. The result shows that only effective follower are essential for an organization, and they are able to give some influence to the leader. Even the follower can have power over the leader if he or she control something that desired by the leader and this condition can create dependency of the leader to him or her. Many tactics can be used to influence the leader, such as reason, coalition, bargaining, assertiveness, and higher authority. Compensation for effective follower is career development, good personal relationship, and trust from the organization.